Determinasi Faktor dalam mempengaruhi Kinerja Sistem Keuangan Desa (SISKUEDES) - Nst, Anggi Pratama; Malikhah, Ikhah; Aulia, Yurika (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2024)
The research aims to analyze the factors that influence the Performance of the Village Financial System (SISKEUDES) in Tanjung Pura District, Langkat Regency in terms of the variables Quality of Village Apparatus, User Involvement, Top Management Support and Supporting Facilities. Research Methods in research use an Associative Approach. The population in this research is all village officials in Tanjung Pura District who use the SISKUEDES application. The sample in the research was 3 people consisting of the Village Head and Head of Financial Affairs and Financial Affairs Staff in 18 Villages, totaling 54 respondents. Data Collection Techniques Use Questionnaires which are distributed to Respondents for 1 day. The research results simultaneously show that the Quality of Village Apparatus, User Involvement, Top Management Support and Supporting Facilities have a positive and significant effect. Meanwhile, partially, the research results show that the quality of village apparatus, user involvement and supporting facilities have a positive and significant effect on SISKEUDES performance. Top Management Support has no effect on SISKEUDES Performance.